Circuitry Underlying Regulation of the Serotonergic System by Swim Stress - Roche, Michelle (J Neurosci, 2003)
The dorsal raphe nucleus (DR)–serotonin (5-HT) system has been implicated in depression and is dramatically affected by swim stress, an animal model with predictive value for antidepressants. Accumulating evidence implicates the stress-related neuropeptide corticotropin-releasing factor (CRF) in the effect of swim stress on this system. This study investigated neural circuits within the DR that are activated by swim stress as revealed by neuronal expression of the immediate early gene, c-fos. Swim stress increased c-fos expression in the dorsolateral subregion of the DR. The majority of c-fos-expressing neurons were doubly labeled for GABA (85 ± 5%), whereas relatively few were immunolabeled for 5-HT (4 ± 1%), glutamate (0.5 ± 0.3%) or calbindin (1.5 ± 0.3%). Dual immunohistochemical labeling revealed that c-fos-expressing neurons in the dorsolateral DR were enveloped by dense clusters of CRF-immunoreactive fibers and also contained immunolabeling for CRF receptor, suggesting that c-fos-expressing neurons in the DR were specifically targeted by CRF. Consistent with this, the CRF receptor 1 antagonist, antalarmin, prevented swim-stress-elicited c-fos expression in the dorsolateral DR. Together with previous findings that both swim stress and CRF decrease 5-HT release in certain forebrain regions, these results suggest that swim stress engages CRF inputs to GABA neurons in the dorsolateral DR that function to inhibit 5-HT neurons and 5-HT release in the forebrain. This circuitry may underlie some of the acute behavioral responses to swim stress as well as the neuronal plasticity involved in long-term behavioral changes produced by this stress.